PENGEMBANGAN MEDIA CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN MINAT BACA DAN KARAKTER JUJUR (Penelitian D&D untuk Siswa Kelas III SDN Tanah Baru Kota Cirebon) - Nilamsari Ramadhanti; Dadan Djuanda; Ani Nur Aeni (Jurnal Pena Ilmiah, 2022)
The purpose of this study was to determine the development of picture story designs based on local wisdom to increase reading interest in third grade elementary school students, validated by experts. The research uses illustrated story media to increase the attractiveness of students to reading as well as local wisdom in the city of Cirebon. This research uses DD method and ADDIE development design. Based on the results of the design / media expert data processing, the validity criteria for the design or media were obtained by 100%. Meanwhile, based on the results of material expert data processing, the validity criteria for the material were obtained at 97.5%. Then the level of validity of both, namely Very Valid, can be used without revision. Validity is only done once because the results obtained from the two experts are very valid.